A Novel Nanoscale FDSOI MOSFET with Block-Oxide - Jyi-Tsong Lin; Yi-Chuen Eng; Po-Hsieh Lin (Active and Passive Electronic Components)
We demonstrate improved device performance by applying oxide sidewall spacer technology to a block-oxide-enclosed Si body to create a fully depleted silicon-on-insulator (FDSOI) nMOSFET, which overcomes the need for a uniform ultrathin silicon film. The presence of block-oxide along the sidewalls of the Si body significantly reduces the influence of drain bias over the channel. The proposed FDSOI structure therefore outperforms conventional FDSOI with regard to its drain-induced barrier lowering (DIBL), on/off current ratio, subthreshold swing, and threshold voltage rolloff. The new FDSOI structure is in fact shown to behave similarly to an ultrathin body (UTB) SOI but without the associated disadvantages and technological challenges of the ultrathin film, because a thick Si body allows for reduced sensitivity to self-heating, thereby improving thermal stability.